A mixed methods approach to assess the likelihood of testing for STI using self-collected samples among behaviourally bisexual women. (30th January 2015) - Schick, Vanessa; Van Der Pol, Barbara; Dodge, Brian; Baldwin, Aleta; Fortenberry, J Dennis
Abstract : Objectives: Behaviourally bisexual women (women who have sex with women and men (WSWM)) are more likely to report a history of sexually transmitted infections (STI) than women who have sex exclusively with men or exclusively with women. Barriers to care may prohibit WSWM from seeking STI testing. The present study investigated participant willingness to self-collect oral, vaginal and anal samples for STI testing. Methods: Eighty WSWM were recruited from two midwestern locations. After completing an online questionnaire, a subset of the participants were interviewed (n=54) and provided the option to self-collect oral, vaginal and/or anal samples to screen for Chlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis . Results: Over two-thirds (67.5%, n=54) of the participants completed the baseline scheduled and attended the interview. The majority of these participants provided vaginal (87.0%, n=47), oral (85.2%, n=46) and/or anal (61.1%, n=33) samples. Participants with a history of anal play were significantly more likely to provide an anal sample. C. trachomatis infection was identified in the samples of 6.8% (n=3) of the participants including 4.5% (n=2) of the vaginal samples and 3.3% (n=1) of the anal samples. None of the samples were positive for N. gonorrhoeae or T. vaginalis . Participants who reported a recent history of anal sexual behaviour with a male partner were significantly more likely to self-collect an anal sample. Conclusions: Given the comparatively high STI rates among WSWM, self-sampling in non-traditional settings may present a unique opportunity to provide needed care to this underserved population of women.